assume S = sum of the numbers
assume n = n number
assume a = first number
assume d = the difference between the next and before number
first number is (a)
second number is (a + d)
third number is (a + 2d)
fourth number is (a + 3d)
n number is [a + (n - 1)d]
(a), (a + d), (a + 2d), (a + 3d), ..................[a + (n - 1)d]
the sum of n number is
equation (1)
S = (a) + (a + d) + (a + 2d) + (a + 3d) + ...........+ [a + (n - 1)d]
equation (2) sum n of number from the last number
S = [a + (n - 1)d] +............+ (a + 3d) + (a + 2d) + (a + d) + (a)
equation (1) + equation (2)
2S = {[2a + (n - 1)d] + [2a + (n - 1)d] +..............+ [2a + (n - 1)d]}
[a + (n - 1)d] repeat n times to get 2S
so, 2S = n[2a + (n - 1)d]
S = (n/2)[2a + (n - 1)d]
from the information that u you gave, a = 1 and d = 2
substitute a = 1 and d = 2 to S = (n/2)[2a + (n - 1)d]
so, S = (n/2)[2(1) + (n - 1)(2)]
= (n/2)[2 + 2n - 2]
= (n/2)(2n)
= n^2
the answer is 1+3+5+...+(2n-1) = n^2
you can try whether that is a equation by substitude the number of n.
for example, the sum for the first 3 numbers is 1 + 3 + 5 = 9
by using the equation you can get n^2 = 3^2 = 9
the sum for the first 4 numbers is 1 + 3 + 5 + 7= 16
by using the equation you can get n^2 = 4^2 = 16
the sum for the first 5 numbers is 1 + 3 + 5 + 7 + 9= 25
by using the equation you can get n^2 = 5^2 = 25
from the example above, we can notice that the equation S = n^2 is correct.
i hope you will understand what i have explained.
2006-11-28 14:50:13
·
answer #1
·
answered by csp 2
·
0⤊
0⤋
As other have said, you can add the end pair together to get 2n and there are (1/2)*n pairs for a sum of n*n.
But you can also do this visually.
Draw a square. Now add to the square by drawing squares to the top and right of the square. You added 3 to get a 2*2 square.
Add more squares(5) to get a 3*3 square.
As you add the odds numbers, as you add the nth odd number, you get n*n.
And now for some extra fun.
If (2n-1) is an odd perfect square(such as 9 or 25)
1+3+5 +7 +9 =25
(1+3+5+7) +9 =25
16 +9 = 25 This is a Pythagorean triplet
1+3 +5+7+9+11+13+15+17+19 +21+23+25 =169
(1+3 +5+7+9+11+13+15+17+19 +21+23)+25 =169
144 + 25 =169 This is also a Pythagorean triplet
This is a proof that there are an infinite number of Pythagorean triplets
2006-11-28 14:49:01
·
answer #2
·
answered by PC_Load_Letter 4
·
0⤊
0⤋
[1+3+...+(2n-3)+(2n-1)]
+
[(2n-1)+(2n-3)+..+3+1]
If we add up pairs of terms like that, we end up with 2n + 2n + .. + 2n, repeated n times.
So double the sum is 2n*n, so the sum is n*n.
2006-11-28 14:11:31
·
answer #3
·
answered by stephen m 4
·
1⤊
0⤋
if u already know the answers why are u asking us but here's how to do it in order
P arentheses
E xponents
M ultiplication
D ivision
A ddition
S ubtraction
so when working an algebra problem just remember PEMDAS!
2006-11-28 14:10:55
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
Use induction.
n, n, Sn
---------
1,1
2, 3, 4
3, 5, 13
4, 7, 20
try to find a pattern, then use induction...
2006-11-28 14:48:33
·
answer #5
·
answered by modulo_function 7
·
0⤊
0⤋
sum is the answer :? and its 9+what+(2xn-1)
2006-11-28 14:11:26
·
answer #6
·
answered by mirror ninja,copycat ninja 1
·
0⤊
1⤋